Students’ Spiraling Silence and Willingness to Communicate about Religion in the United States: An Exploration of the Media’s Role in Stigmatizing Religion - Alkazemi, Mariam F. (Journal of religion, media and digital culture, 2013)
The spiral of silence effect describes individuals’ tendency to silence minority opinions, whilst using the media to gauge majority opinion. While the spiral of silence effect has been explored in controversial political contexts, the phenomenon has not been scrutinized in its relation to religious communication. The current study applies this concept to further the current understanding of communication as it applies to religion. A questionnaire was distributed electronically to 94 students at a large university in the southeastern United States. Using survey methods, this paper finds that religiosity is positively correlated to willingness to communicate about religion. This paper also finds that media exposure is not related to either willingness to communicate about religion or religiosity.